Failed states and the origins of violence: a comparative analysis of state failure as a root cause of terrorism and political violence - Howard, Tiffiany (Ashgate, 2014)
Cover; Contents; List of Figures; List of Tables; Acknowledgements; 1 Breeding Grounds: Failed States and the Origins of Terrorism and Political Violence; 2 And They All Fall Down: The Pandemic of Political Violence and State Failure in sub-Saharan Africa; 3 A Legacy of Tyranny, Tragedy and Terror: A Closer Look at Weak States, Authoritarian Rule, and Radical Religious Terrorism in the Middle East and North Africa; 4 Crouching Tiger, Hidden Dragon No More: The Emerging Crisis of Collapsed States and Extremist Terrorism in Southeast and South Asia